Graphene oxide–Li+@C60 donor–acceptor composites for photoenergy conversion1. Issue 24 (28th June 2015) - Supur, Mustafa; Kawashima, Yuki; Ohkubo, Kei; Sakai, Hayato; Hasobe, Taku; Fukuzumi, Shunichi
<x xml:space="preserve">Abstract</x> An ionic endohedral metallofullerene (Li+@C60) with mild hydrophilic nature was combined with graphene oxide (GO) to construct a donor–acceptor composite in neat water.